For inclusion we need more society e less technology: technology doesn’t solve social inequalities - Maria João Simões; Martins A.F.; Faustino, Délcio (GKA TECHNO 2019 MADRID, 9th International Congress on Technology, Science and Society, 2019)
Our aim is, on the one hand, to map paths of technological inequality and the ethical challenges posed by technological development, highlight that it is simplistic to think that the inequalities or the reduction of the harmful effects of some technologies can be detected only after the technologies are available, through innovative social solutions. On the other hand, it is also relevant to identify the interests and purposes underlying the creation / development of (new) technologies that may deepen or create new inequalities and to raise unavoidable ethical issues; in this sense mechanisms of public participation should be created allowing citizens to pronounce on technological choices. Our reflection will be made taking into account some of the (new) technologies that are emerging. We will first analyse ICTs, which have emerged associated with a libertarian ideology and in the belief of an egalitarian access to information and knowledge for all. It is a technologically deterministic view that does not take into account that we live in societies with structural inequalities difficult to mitigate. Regarding access issues, inequalities of use are underestimated although they are much more difficult to overcome. Despite the importance of inclusive and punctual social measures, as recent empirical studies point out, effective social and educational policies are needed to reduce such inequalities. Secondly, we will analyse the new technological developments in the field of biotechnology, artificial intelligence and robotics, linked to powerful interest groups, where new and deeper social inequalities are experienced, as well as ethical and legal issues. Lastly, we will examine, on the one hand, how algorithms are not neutral and are a source of more inequalities and, on the other hand, the (new) inequalities relating with surveillance processes, and how we may become less autonomous citizens, which entails a threat to democracy.